Nonlinear analysis of reinforced concrete slabs through the finite element method - Hernandorena Viegas, Carlos Henrique; Real, Mauro de Vasconcelos; Titello, Eduardo Pagnussat (International Journal of Advanced Engineering Research and Science, 2022)
One of the significant difficulties in representing the behavior of reinforced concrete structures in mathematical models is the post-cracking non-linearity. And so, reinforced concrete slabs are no exception to the rule. Still, the usual analysis models for this structural element are verified in the elastic regime when the concrete tensile strength is considered. This model is acceptable for the service limit states but not the ultimate limit state. These aspects associated with the great difference in the behavior of concrete when subjected to tension or compression make it necessary to study a nonlinear mathematical model that can represent a reinforced concrete slab subjected to bending, from the beginning of loading until its failure, as accurately as possible. With this, the ANSYS software, from its version 18, made available in its library the Drucker-Prager-Rankine model arranged with two distinct rupture surfaces. A Drucker-Prager criterion for the concrete subjected to compression and a Rankine criterion for concrete in tension. In addition, the software is based on the finite element method, giving the possibility of precise and nonlinear analysis through load and deformation increments, taking into account both elastic and plastic deformations after concrete cracking. Thus, this work aims to present the modeling of reinforced concrete slabs through the Drucker-Prager-Rankine surface, validating the model by comparing it with several experimental tests. The model results were coherent and acceptable, presenting a good approximation of the results of the tests.